„Świerszczyk. Tygodnik dla dzieci” – powojenna rzeczywistość i kształtowanie światopoglądu odbiorcy na łamach rocznika 1945 - Ungeheuer-Gołąb, Alicja (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
This article focuses on Świerszczyk, a Polish magazine for children. It explores the development of the magazine, and further analyses the 1945 content of the magazine. Specifically, the researcher concentrates on the thematic focus of poetry and prose content in the magazine and lists the names of writers and poets who published their works in the first issues of the magazine. The authoress identifies the ways that adult creators frame messages for young readers as well as the potential influence of the messages they convey on young readers in post-war Poland. She draws conclusion on reorientating topics in line with social needs and ideology.